Delayed Auditory Brainstem Responses (ABR) in children after sight-recovery. (10th December 2021) - Martinelli, A.; Bianchi, B.; Fratini, C.; Handjaras, G.; Fantoni, M.; Trabalzini, F.; Polizzi, S.; Caputo, R.; Bottari, D.
Abstract: Studies in non-human animal models have revealed that in early development, the onset of visual input gates the critical period closure of some auditory functions. The study of rare individuals whose sight was restored after a period of congenital blindness offers the rare opportunity to assess whether early visual input is a prerequisite for the full development of auditory functions in humans as well. Here, we investigated whether a few months of delayed visual onset would affect the development of Auditory Brainstem Responses (ABRs). ABRs are widely used in the clinical practice to assess both functionality and development of the subcortical auditory pathway and, provide reliable data at the individual level. We collected Auditory Brainstem Responses from two case studies, young children (both having less than 5 years of age) who experienced a transient visual deprivation since birth due to congenital bilateral dense cataracts (BC), and who acquired sight at about two months of age. As controls, we tested 41 children (sighted controls, SC) with typical development, as well as two children who were treated (at about two months of age) for congenital monocular cataracts (MC). The SC group data served to predict, at the individual level, wave latencies of each BC and MC participant. Statistics were performed both at the single subject as well as at the group levels on latencies of main ABR waves (I, III, V and SN10). Results revealed delayed response latencies for both BC children compared with the SC group starting from the wave III. Conversely, no difference emerged between MC children and the SC group. These findings suggest that in case the onset of patterned visual input is delayed, the functional development of the subcortical auditory pathway lags behind typical developmental trajectories. Ultimately results are in favor of the presence of a crossmodal sensitive period in the human subcortical auditory system. Highlights: Auditory Brainstem Responses (ABR) are delayed in children after sight-recovery. Early lack of patterned visual input alters the development of the auditory system. Visual input might gate crossmodal sensitive periods of auditory development.